Media Audio Visual Interaktif dalam Pembelajaran Membaca Permulaan - Aleda Mawene; Tri Handayani (JURNAL PENGABDIAN PAPUA, 2026)
Students who have developed strong language skills from an early age are expected to become communicative and productive speakers of Indonesian. In reality, there are still students in second grade at SD N Inpres Tanjung Ria in Jayapura City who are still learning to sound out letters and have not yet learned to distinguish between letters correctly. Among the contributing factors is the fact that the use of a variety of reading learning materials has not been implemented to its full potential. This community service project was carried out in first grade at SD N Inpres Tanjung Ria in Jayapura City. This activity aims to: (1) improve the participation and early reading skills of first-grade students at Tanjung Ria Inpres Public Elementary School in Jayapura City through interactive audiovisual media; (2) enhance the competence of first-grade teachers at Tanjung Ria Inpres Public Elementary School in Jayapura City in using interactive audiovisual media. This activity was held on September 4, 2025, from 8:00 a.m. to 10:30 a.m. WIT. This PKM activity employed a mentoring model that combined the Service Learning (SL) and Participation Action Research (PAR) approaches. The results of this community service project indicate that AVI media is suitable for use in differentiated instruction because it can accommodate students’ diverse learning styles. In addition, this media can help develop reading proficiency and engage students in learning at their own pace. This was demonstrated by the students through: (1) showing excitement when the teacher launched the AVI media; (2) showing interest and a desire to try the AVI media; (3) paying attention when their classmates practiced reading activities using the AVI app; (4) demonstrating confidence in using the AVI media; (5) practicing more than two sections of the AVI application; (6) asking the teacher to continue practicing reading activities with the AVI application. The procedure for using the AVI media in early reading instruction consists of: (1) the Preparation Stage, (2) the Material Delivery Stage, (3) the Evaluation and Follow-Up Stage. It was concluded that this AVI media is very engaging and motivates students to learn to read. The learning stages are simple and easy to implement, so they can be mastered well and effectively by classroom teachers. It is hoped that AVI media, particularly the Reading Learning Application, can be implemented in first grade during the next school year.